Design and Evaluation of a Continuous Fibre Reinforced Thermoplastic Prepreg Manufacturing Line - Tian, Ran (Université d'Ottawa / University of Ottawa, 2022)
Thermoset resin based fibre reinforced polymer-matrix composite materials (PMCs) have provided excellent solutions to many industries based on their great specific strength, high design freedom and other characteristics such as water resistance, corrosion resistance, tailorable electrical conductivity, tailorable thermal performance and many others. But, despite of all their benefits, the materials are also limited by uneconomical recycling and management post service life, demanding raw materials storage conditions, less than ideal environmental impact during manufacturing, and relatively low productivity. The purpose of the present work was to investigate economically feasible production of a continuous fibre reinforced thermoplastic composite (CFRTP) alternative solution, for an existing company, that could overcome weak points and limitations of thermosets under increasing environmental needs and pursuit of higher efficiency. Work aimed at fulfilling the following objectives: 1) document existing thermoplastic composite materials and understand selected manufacturing methods, raw materials, mechanical behaviour and operational feasibility; 2) select, design, and build a fully functional CFRTP manufacturing line; 3) design and run Taguchi methods to analyze the product using multifactorial ANOVA to gently introduce rigorous quality control; and 4) identify the input parameters that most affect output product quality, that could be used to optimize the process, as well as input parameters that have no statistically significant effects on the output and therefore do not warrant investment in funds and time in order to control them. Throughout the work, it was showed that CFRTP could been produced efficiently with consistent quality. Unidirectional prepreg can be used directly or further processed for usage in many industries such as pipelines, light construction and automotive components. The design of the CFRTP solution fulfilled necessary conditions and successfully produced CFRTP unidirectional prepreg product. Prepreg produced under 16 different sets of conditions was tested and data was collected. Using Taguchi methods, this study found that the fibre volume fraction, condition of impregnation mould, condition of cooling rollers and extruding temperature all have statistically significant effects on product quality. But limited by restriction from time and cost by production based environments, it is imperative to conduct this work perfectly, in later research a more focused study can be done based on the results of this study. Still, thesis demonstrates a CFRTP mass production solution, verifies CFRTP impregnation and offers a significant route for upgrading environmental protection and production efficiency. The work also identifies key parameters that affect unidirectional prepregs properties.
Keywords: Continuous Fibre Reinforced Thermoplastic; Thermoplastic Composites; CFRT; Taguchi Method